2013
DOI: 10.11111/jkana.2013.19.3.382
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research on Self-leadership in Nurses'

Abstract: The purpose of this study was to review journal articles, master's theses, and doctoral dissertations on self-leadership in nurses in order to identify overall trends in nursing self-leadership and to suggest strategies to improve self-leadership. Methods: Twenty-six papers on self-leadership in nurses were reviewed. Results: These papers were journal articles, master's theses, and doctoral dissertations regarding nurses who worked in general hospitals, university hospitals, and public health centers. Self-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 10 publications
1
7
0
3
Order By: Relevance
“…In this study, self‐leadership was higher for those over 40 years of age than for those 39 and under, and self‐leadership was higher when academic achievement, clinical experience and preceptor experience were higher. These findings are consistent with those of a previous study that showed that the higher the age, career level and education level, the greater the self‐leadership of nurses (Won & Cho, ). Self‐leadership, unlike personality characteristics can change with training (Neck & Houghton, ); the higher the career and education level, the more autonomous power there is to increase learning ability and achievement as part of continuous self‐development efforts.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, self‐leadership was higher for those over 40 years of age than for those 39 and under, and self‐leadership was higher when academic achievement, clinical experience and preceptor experience were higher. These findings are consistent with those of a previous study that showed that the higher the age, career level and education level, the greater the self‐leadership of nurses (Won & Cho, ). Self‐leadership, unlike personality characteristics can change with training (Neck & Houghton, ); the higher the career and education level, the more autonomous power there is to increase learning ability and achievement as part of continuous self‐development efforts.…”
Section: Discussionsupporting
confidence: 93%
“…Self‐leadership, unlike personality characteristics can change with training (Neck & Houghton, ); the higher the career and education level, the more autonomous power there is to increase learning ability and achievement as part of continuous self‐development efforts. These results suggest that self‐leadership is thereby enhanced (Won & Cho, ), and a similar phenomenon seems to hold for nursing preceptors.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…셀프리더 십에 대한 연구는 주로 경영학에서 시작되었고, 간호조직을 대상으로 연구를 한 결과 간호사의 직무만족, 조직몰입을 높 이고 간호업무의 효율성과 생산성 향상을 증진시키는 것으로 나타났다 (Won & Cho, 2013). 또한, 간호 대학생의 임상실습 스트레스를 감소시키고 문제 해결과 대학생활 적응을 도우며, 개인의 발전에 지속적으로 긍정적 영향을 주는 것으로 나타 났다 (Lee & Cho, 2012;Won & Cho, 2013;Yang & Moon, 2011).…”
Section: 한편 최근 리더십 이론 중에서 중요성이 증가하고 있는 셀 프리더십은 개인 스스로가 자율적으로 자신을 리드하unclassified